DESIGN AND CONSTRUCTION OF A MICROCONTROLLER-BASED ALTERNATING CURRENT (AC) ELECTRIC MOTOR AS A CORN THRESHING TOOL - Ardiansa; Ratih Puspita Siwi; Ainur Fajri Fauzan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The integration of Bulukumba Regency area, especially in Laikang Village, Kajang District, is one of the vast corn farming areas because it is located in a mountainous area. Corn is one of the food crops as a substitute for rice, besides corn is also used as animal feed. In general, farmers thresh corn manually (human power) without using machine tools, so it requires a lot of energy, time and very low production results, so that the manual corn threshing method becomes inefficient. One alternative that must be done is to design a microcontroller-based corn threshing machine. This study aims to design a microcontroller-based Alternating Current (AC) Electric Motor as a corn threshing tool that functions to separate corn kernels from the cob so that it can accelerate production in corn threshing. This study uses an experimental method that explains systematic and planned experiments to prove the truth of a theory. Respondents in this study were farmer groups in Laikang Village, Kajang District, Bulukumba Regency. This study has 6 stages, namely: 1) implementation of research preparation; 2) research permit; 3) field observation; 4) data collection techniques; 5) data processing; and 6) research results. Based on the trial results, farmers stated that the design of a microcontroller-based alternating current (AC) electric motor as a corn threshing tool functioned well.